The Effectiveness of Online Playing Storytelling Card on Student’s Vocabulary Mastery: An Experimental Research at SMAN 2 Bengkulu - Fika Mardhiyah Ulfah; Edi Trisno (Journal of English Language Teaching, 2020)
Online playing storytelling card is the instructional tool that can be used in language learning. The purpose of the research is to find out whether or not online playing storytelling card is effective on students’ vocabulary mastery at SMAN 2 Bengkulu. This research was pre-experimental research with one group pretest-posttest design. The instrument used in this research was test and to collect the data, theresearcher used rubric as modified from Marek& Wu (2014). In order to determine the successful of the research, the researcher did the one group multiple testing design in this research. Thus, in this research, there are three posttest that are already administered. Based on the data analysis, there is a significant effect of using online playing storytelling card on student’s vocabulary mastery. It was proved that the mean of student’s pretest and student’s total posttest was very significantly different. The mean of student’s pretest was 19,60, Then, the first posttest was 21,7667. The second posttest was 23,50 and the third posttest was 25,9333. Then, the three of Sig. (2-tailed) scores were 0,000 which lower than the determined significance value 0.05.